Diabetic Myonecrosis Involving Both Lower Limbs in Hemodialysis Patient: A Rare Complication of Diabetes. - Chowdhury, Md Farhad Hasan; Anwar, Mohammed Rashed; Hossain, Momtaz; Deb Nath, Palash Kumar; Nargis, Tania (Mugda Medical College Journal, 2023)
Diabetic myonecrosis (DMN) is the term used for spontaneous ischemic necrosis of skeletal muscle, unrelated to atheroembolism or occlusion of major arteries. DMN is a rare microangiopathic disorder that can present as an acutely painful and swollen limb in patients with established diabetes mellitus. Muscles of the thighs are commonly affected in DMN. The condition can be diagnosed noninvasively with magnetic resonance imaging and resolves with analgesia, bed rest, and glycemic control. The majority of patients with DMN have diabetic nephropathy, yet this condition is not widely recognized. Due to uncommon presentation, lack of specific marker of investigation, diagnosis is often missed, resulting in unnecessary and deleterious interventions such as antibiotics, muscle biopsies, and surgery; the latter two of which can prolong recovery. Here, we report a patient on hemodialysis who is ultimately diagnosed as DMN affecting both lower limb and treated successfully. Mugda Med Coll J. 2022; 5(2): 113-116